Assessment of Nutritional Value of Limonia acidissima L. (Wood Apple) (Dhaka University Journal of Science, 2022)
The objective of the study was to investigate Limonia acidissima L. (wood apple) to determine the moisture and ash content, total amount of carbohydrates, fatty acid compositions, the quantity of protein and micronutrients (Na, K, Zn, Fe) present in wood apple grown in Bangladesh. FT-IR spectroscopy was used to pinpoint many biologically significant functional groups. The moisture and ash content obtained were 74.02 and 25.44%, respectively. Carbohydrate content determined by ultraviolet-visible (UV-Visible) spectroscopic method was 16.14 g per 100 g of dried fruit sample. The fatty acids were identified by Gas Chromatography-Flame Ionization Detector (GC-FID). The relative percentage of bound fatty acids mainly palmitoleic acid, octadecanoic acid, cis-9-oleic acid and octanoic acid were 17.33, 15.09, 15.09 and 45.09%, respectively. The amount of protein was 5.11%. The micronutrients such as Na, K, Zn, Fe present in the edible portion of wood apple measured by atomic absorption spectroscopy (AAS) were 10.40, 58.24, 0.37 and 1.67 mg per 100 g of dried sample, respectively. The fruit has long been utilized in herbal medicines and is eaten raw or processed into various products to prevent noncommunicable diseases and micronutrient deficiencies.Dhaka Univ. J. Sci. 70(2): 48-52, 2022 (July)